High flow nasal oxygen (HFNO) in the treatment of COVID-19 infection of adult patients from – An emergency perspective: A systematic review and meta-analysis - Nabil, Shallik (2023)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2, which was first discovered in Wuhan, China. The disease has grown into a global pandemic causing mild to moderate symptoms in most people. The disease can also exhibit serious illnesses, especially for patients with other chronic diseases such as cardiovascular diseases, diabetes, chronic respiratory disease, or cancer. In such cases of severe illness, high flow nasal oxygen (HFNO) has been used to provide oxygenation to COVID-19 patients. However, the efficiency of HFNO remains uncertain, prompting the conduction of this systematic review to evaluate the effectiveness of the therapy.A thorough search for relevant and original articles was carried out on five electronic databases, including ScienceDirect, PubMed, Cochrane Library, Embase, and Google Scholar. No time limitation was placed during the search as it included all the articles related to COVID-19 from 2019 to 2022. The search strategy utilized in this systematic review yielded 504 articles, of which only 10 met the eligibility criteria and were included. Our meta-analysis reveals that HFNO success rate was higher than HFNO failure rates (0.52 (95% CI; 0.47, 0.56) and 0.48 (95% CI; 0.44, 0.53), respectively), however, the difference was statistically insignificant. HFNO was associated with a significant decrease in mortality and intubation rates (0.28 (95% CI; 0.19, 0.39) and 0.28 (95% CI; 0.18, 0.41), respectively). Our statistical analysis has shown that significantly lower ROX index (5.07 ± 1.66, p = 0.028) and PaO2/FiO2 (100 ± 27.51, p = 0.031) are associated with HFNO failure, while a significantly lower respiratory rate (RR) (23.17 ± 4.167, p = 0.006) is associated with HFNO success. No statistically significant difference was observed in SpO2/FiO2 ratio between the HFNO success and failure groups (154.23 ± 42.74 vs. 124.025 ± 28.50, p = 0.62, respectively).Based on the results from our meta-analysis, the success or failure of HFNO in treating COVID-19 adult patients remains uncertain. However, HFNO has been shown to be an effective treatment in reducing mortality and intubation rates. Therefore, HFNO can be recommended for COVID-19 patients but with close monitoring and should be carried out by experienced healthcare workers.